Modelling scenarios of environmental recovery after implementation of controls on emissions of persistent organic pollutants. Issue 9 (14th August 2020) - Comber, S. D. W.; Gardner, M. J.; Constantino, C.; Firth, S.; Hargreaves, A.; Davies, R.
Abstract : Predictions of BaP concentrations in biota decreasing towards the EQS over time. Abstract : Comparison of monitoring data with toxicologically-derived environmental quality standards (EQSs) forms the basis of assessments of the quality status of the water environment. Having established the status quo, the logical next step is to address instances of non-compliance with EQSs by applying remedial measures, including reducing the use or at least the emission of the substances of concern or by taking steps to reduce concentrations already present using technological solutions such as enhanced wastewater treatment. The selection of suitable remedial measures must be a compromise between cost, likely effectiveness and the timescale over which improvements might be acceptable. The decision on overall environmental management has also to take into account the need for demonstrable progress; this might mean that it is preferable to address some more readily achievable goal rather than to attempt to solve a more serious, but ultimately intractable problem. This paper describes the development and application of a generic modelling tool that provides a way of assessing the potential requirements for remedial actions and their likely outcomes over a timescale of up to forty years taking account of sediment partitioning, environmental degradation and biological accumulation. The tool was validated using a detailed UK wastewater treatment works effluent discharge dataset. Examples involving several chemicals that are of current concern are provided. Some substances ( e.g. tributyltin, PFOS) are identified as likely to meet EQS values in sediments or biota in a relatively short timescale; others (PAHs, DEHP) appear to represent more intractable problems.